Le caballito de totora à Huanchaco, une embarcation singulière et une pratique de pêche millénaire au Pérou - Marina Quiñe (Revue d'ethnoécologie)
In Peru, fishing has been practiced for more than ten thousand years and still represents one of the most important economic activities. In this paper we are interested in an ancestral fishing practice that persists in time without any significant variation: fish riding on a boat called caballito de totora, in Huanchaco, Peru. We focus on acquiring better knowledge about the boat, el caballito de totora, which has maintained its structure and craftsmanship for more than two thousand years.